Shoot multiplication as affected by different explant position on mother stock plant of Clinacanthus nutans - Ismail, Mohamad Zamir Hadi (2017)
Clinacanthus nutans of the family Acanthaceae or commonly known as Sabah Snake Grass is a famous tropical herb used for medicinal purpose. This plant is widely used in Southeast Asia especially in Malaysia as an anti-inflammatory drug for the treatment of wound and disinfection. Recently, it is used in treating cancer. This plant is usually propagated by stem cutting which has low reproductive capacity. The development of rapid propagation methods for C. nutans is required to satisfy human demand for its medicinal products. The purpose of this study is to establish an effective protocol for in vitro multiplication of C. nutans shoots. The study is conducted by sub-culturing different explants of C. nutans on Murashige & Skoog 1962 (MS) medium added with 2 mg/L 6-Benzylaminopurine (BAP). Shoot tip and different node positions on stock plant of C. nutans are used as the explants. The study is conducted using a Completely Randomized Design. The cultures are maintained for 8 weeks in the culture room with a light intensity of 30μmol/m²/s. It is observed that the number of shoot proliferated was significantly higher (p<0.05) when using shoot tip explant compared to node explants excised at different position on the mother stock plant. The shoot tip explant is the best explant for inducing shoot proliferation. Sub-culture of the explant needs to be carried out at sixth till seventh week.